1990
DOI: 10.1109/50.54518
|View full text |Cite
|
Sign up to set email alerts
|

Interlaboratory comparison of radiation-induced attenuation in optical fibers. III. Transient exposures

Abstract: A comparison of the losses induced in step-index multimode, graded-index multimode, and single-mode fibers by pulsed radiation exposure has been made among 12 laboratories over a period of five years. The recoveries of the incremental attenuations from to 10' s are reported. Although a standard set of measurement parameters was attempted, differences between the laboratories are evident; possible origins for these are discussed.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0
1

Year Published

1991
1991
2007
2007

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 50 publications
(13 citation statements)
references
References 13 publications
0
12
0
1
Order By: Relevance
“…4,15,16,17 Work is in progress establishing future standards for measuring the effects of steady state and transient ionizing radiation on optical fibers. Measurements performed on multimode and single mode practical optical fibers reveal that radiation dose rates and injected optical power levels significantly influence induced attenuation in silica core fibers.…”
Section: Optical Fiber Waveguidementioning
confidence: 99%
“…4,15,16,17 Work is in progress establishing future standards for measuring the effects of steady state and transient ionizing radiation on optical fibers. Measurements performed on multimode and single mode practical optical fibers reveal that radiation dose rates and injected optical power levels significantly influence induced attenuation in silica core fibers.…”
Section: Optical Fiber Waveguidementioning
confidence: 99%
“…Typical light power in the fiber was 10 mW; this light level is typical of the level required to fully drive modern, highbandwidth photoreceivers after demodulating the phase using an interferometer based on a 3 × 3 coupler as we have done. Prior studies [1] have suggested that this constitutes "high-power" operation of fiber links, but the design of a system around commercially available components and digitizers drives the decision to use approximately 1 mW per photoreceiver, with the optical signal typically split between two or more receivers.…”
Section: Methodsmentioning
confidence: 99%
“…For a 30-m fiber run, the transit time dominates this expression, so for the purposes of this study, we concern ourselves with effects only during the initial 150 ns. Survivability of the link over many shots is a separate concern that is addressed by a variety of studies in the literature [1], [2], [9].…”
Section: Magnitude Of Radiation Effects On Transmission Fibersmentioning
confidence: 99%
See 1 more Smart Citation
“…Ainsi, une fibre optique adéquate pour une application sous un environnement spécifique peut ne pas l'être pour un autre type d'irradiation. En particulier, la réponse transitoire (t < 100 ms) des fibres optiques après une impulsion ionisante est beaucoup moins documentée que celleà la dose cumulée [6][7][8]. Dans cet article, nous comparons la tenue de fibres commerciales ou issues de laboratoires R&Dà deux environnements possédant des débits de dose très différents (10 -1 Gy/s et > 10 6 Gy/s) mais des doses et desénergies comparables (< 1 kGy ; ∼1 MeV).…”
Section: Introductionunclassified